INEXTENSIBLE FLOWS OF CURVES IN THE EQUIFORM GEOMETRY OF THE PSEUDO-GALILEAN SPACE G13 - Öztekin, Handan; Bozok, Hülya Gün (Işık University Press, 2016)
In this paper, we study inextensible ows of curves in 3-dimensional pseudo- Galilean space. We give necessary and su cient conditions for inextensible ows of curves according to equiform geometry in pseudo-Galilean space.